STRANGERS IN ROME: THE ATTITUDE OF THE ROMANS TOWARDS IMMIGRANTS IN LATE ANTIQUITY (ACCORDING TO AMMIANUS MARCELLINUS) - Dmitriev, Vladimir; Alieva, Liudmila (Revista Inclusiones, 2020)
The last great Roman historian Ammianus Marcellinus (ca. 330 – ca. 400) in his monumental work “Res gestae” gave a prominent place to the description of life and customs of contemporary Roman society. The writer pays special attention to the attitude of the Romans towards immigrants. Ammianus’ attention to the issue is due to the fact that he was not a native of the city of Rome, and the Roman city community perceived him as a stranger throughout his life. However, when Ammianus accuse the Romans of xenophobia, he is not guided solely by personal hostility. Hostile attitude towards strangers resettled to Rome was a characteristic of the Roman mentality as a whole. In the eyes of the citizens and authorities of Rome, the immigrants have a lower status than any native Roman, and sometimes xenophobia became one of the basic principles of Roman domestic policy. The strengthening of xenophobic attitudes within the Roman society Ammianus connects with the crisis of the Roman value system in the contemporary period. One more reason for the increase in xenophobia in Late Rome consisted in increasing the barbarization of the Empire and the massive penetration of barbarians into diverse spheres of the life of Roman society. The extremely negative attitude of the Romans towards immigrants was also due to the intensification of the onslaught of barbarian tribes on the borders of the Empire in the 3rd – 4th centuries AD.